Monitoring Perangkat Jaringan Menggunakan Fitur Bot Telegram Berbasis Mikrotik - Adi Wibowo (Sienna, 2021)
The use of computer networks is increasingly growing, this causes the installation of network devices to be more and more diverse. With so many network devices installed, the risk of damage that occurs makes network administrators take a long time to detect the damage. To overcome this, it is possible to create a Telegram Bot for monitoring mikrotik and other devices connected to the networks. Mikrotik OS through script logic that is inputted through the features can inform network damage to network administrators. Telegram bot is a bot or robot that is programmed with various commands to carry out some instructions given by the user. By using bots, you can perform network management on Mikrotik, making it easier for a network administrator to work. This study aims to monitor network devices, send notification messages that enter the Telegram application to be able to find out the status of active and inactive users and devices.